The geography of ethnic violence : identity, interests, and the indivisibility of territory - Toft, Monica Duffy, 1965- (Princeton University Press, 2003)
The Geography of Ethnic Violence is the first among numerous distinguished books on ethnic violence to clarify the vital role of territory in explaining such conflict. Monica Toft introduces and tests a theory of ethnic violence, one that provides a compelling general explanation of not only most ethnic violence, civil wars, and terrorism but many interstate wars as well. This understanding can foster new policy initiatives with real potential to make ethnic violence either less likely or less destructive. It can also guide policymakers to solutions that endure. The book offers a distinctively.